ORIENTASI KARIR MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING IKIP PGRI PONTIANAK - Hendra Sulistiawan; Kamaruzzaman Kamaruzzaman (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThis research was conducted based on empirical findings which showed that the problemof the low career orientation of students. Therefore it is necessary to know clearly inaddressing the situation, so that problems related to career orientation experienced bystudents can be analyzed in depth. This study aims to determine the career orientationof the Guidance and Counseling Study Program students. The method used in thisresearch is descriptive method in the form of survey research. Research Subjects arestudents of guidance and counseling study program Academic Year 2019/2020. Basedon the analysis of the data in the study it can be concluded that career orientation isincluded in the sufficient category. This can be interpreted that career awareness, careerexploration, and student career planning are quite good.Keywords : career orientation, student guidance and counseling.